Combination therapy for inhibitor reversal in haemophilia A using monoclonal anti-CD20 and rapamycin - Biswas, Moanaro; Rogers, Geoffrey L.; Sherman, Alexandra; Byrne, Barry J.; Markusic, David M.; Jiang, Haiyan; Herzog, Roland W. (Thrombosis and Haemostasis, 2017)
Development of antibodies (inhibitors) against coagulation factor VIII (FVIII) is a major complication of intravenous replacement therapy in haemophilia A (HA). Current immune tolerance induction (ITI) regimens are not universally effective. Rituximab, a B cell-depleting antibody against CD20, has shown mixed results for inhibitor reversal in patients. This study aims to develop a combinatorial therapy for inhibitor reversal in HA, using anti-murine CD20 (anti-mCD20) antibody and rapamycin, which targets both B and T cell responses. Additionally, it extensively characterises the role of the IgG backbone in B cell depletion by anti-CD20 antibodies. For this, inhibitors were generated in BALB/c-HA mice by weekly IV injection of FVIII. Subsequently, anti-mCD20 (18B12) with IgG2a or IgG1 backbone was injected IV in two doses three weeks apart and B cell depletion and recovery was characterised. Rapamycin was administered orally 3x/week (for 1 month) while continuing FVIII injections. Altering the IgG backbone of anti-mCD20 from IgG2a to IgG1 reduced overall depletion of B cells (including memory B cells), and marginal zone, B-10, and B-1b cells were specifically unaffected. While neither antibody was effective alone, in combination with rapamycin, anti-mCD20 IgG2a but not IgG1 was able to reverse inhibitors in HA mice. This regimen was particularly effective for starting titres of ∼10 BU. Although IgG1 anti-mCD20 spared potentially tolerogenic B cell subsets, IgG2a directed sustained hyporesponsiveness when administered in conjunction with rapamycin. This regimen represents a promising treatment for inhibitor reversal in HA, as both of these compounds have been extensively used in human patients.Supplementary Material to this article is available at www.thrombosis-online.com.
Keywords: Anti-mCD20; factor VIII; haemophilia; inhibitor; rapamycin